One-Step Synthesis and Characterization of Polyaniline Nanofiber/Silver Nanoparticle Composite Networks as Antibacterial Agents - Poyraz, Selcuk; Çerkez, İdris; Huang, Tung Shi; Liu, Zhen; Kang, Litao; Luo, Jujie (Amer Chemical Soc, 2014)
Through a facile and effective seeding polymerization reaction via a one-step redox/complexation process, which took place in aqueous medium at ambient temperature, silver nanoparticles (Ag NPs) embedded polyaniline nanofiber (PANI NF) networks were synthesized as antibacterial agents. During the reaction, not only NF morphology formation of the resulting conducting polymers (CPs) but also amplification of the aqueous silver nitrate (AgNO3) solutions oxidative potentials were managed by vanadium pentoxide (V2O5) solgel nanofibers, which acted as well-known nanofibrous seeding agents and the auxiliary oxidative agent at the same time. The PANI/Ag nanocomposites were proven to exhibit excellent antibacterial property against both Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. Antibacterial property performance and average life span of the nanocomposite network were optimized through the homogeneous distribution/embedment of Ag NPs within one-dimensional (1-D) PANI NF matrix. The antibacterial efficacy tests and nanocomposite material characterization results further indicated that the sole components of PANI/Ag have a synergistic effect to each other in terms of antibacterial property. Thus, this well-known catalytic seeding approach via a one-step oxidative polymerization reaction can be considered as a general methodology and a substantial fabrication tool to synthesize Ag NP decorated nanofibrillar PANI networks as advanced antibacterial agents.
Keywords: silver nanoparticle; polyaniline nanofiber; nanocomposite; antibacterial property